Linguistic Priming and Learning Adjacent and Nonadjacent Dependencies in Serial Reaction Time Tasks. Issue 3 (3rd March 2022) - Wang, Felix Hao; Kaiser, Elsi
Abstract: Although syntactic priming has been well studied and is commonly assumed to involve implicit learning, the mechanisms behind this phenomenon are still under debate. Recent studies have suggested that exposure to nonlinguistic statistical patterns may influence language users' relative clause attachment biases, but whether the priming effect comes from implicit learning or explicit experimental task demands has remained unclear. In this study, we tested whether implicit learning of adjacent and nonadjacent sequences occurs in a nonlinguistic task (the serial reaction time task), and if so, whether these implicitly learned dependencies can cause syntactic priming in the linguistic domain. We found no priming effects even though dependencies in the serial reaction time task were successfully learned: learning of nonlinguistic dependencies did not prime relative clause attachment biases when dependency learning was strictly implicit in nature. This work provides novel evidence that implicit knowledge from a domain‐general sequencing task alone does not necessarily induce syntactic priming. Abstract :